(untitled) (Vietnam Journal of Community Medicine, 2025)
Introduction: The global disease pattern is continuously shifting, imposing a significant burden on healthcare systems. Ha Dong General Hospital is a Grade I hospital situated in the southwestern area of Hanoi, primarily serving insured patients. Analyzing the disease patterns among inpatients is essential for hospital planning and development, particularly as the hospital operates under the Group 2 financial autonomy model. Objective: To describe the disease pattern among inpatients at Ha Dong General Hospital in 2023. Methods: A cross-sectional descriptive study was conducted using retrospective data from electronic medical records stored at Ha Dong General Hospital between January 1 and December 31, 2023. Records that met the inclusion and exclusion criteria were classified into 22 ICD-10 chapters and analyzed to identify the five most common diagnoses. Results: In 2023, the hospital recorded 40,048 inpatient visits. The highest proportions of visits fell under Chapter XV: Pregnancy, Childbirth, and the Puerperium (17%) and Chapter I: Certain Infectious and Parasitic Diseases (16%). The five most common diagnoses were Dengue fever (10.64%), Pneumonia with unspecified organism (2.39%), Diabetes mellitus Type 2 (2.05%), Acute bronchitis (1.76%), and Other bacterial intestinal infections (1.55%). Conclusion: The disease pattern among inpatients at Ha Dong General Hospital in 2023 demonstrates a double disease burden, characterized by increasing rates of non-communicable diseases (NCDs) alongside persistent infectious diseases. To address this trend, strategic adjustments in resource allocation and workforce development are essential. Additionally, enhancing chronic disease management models is critical to managing the growing population with NCDs effectively.